URGENSI KESADARAN BUDAYA DALAM LAYANAN BIMBINGAN DAN KONSELING [THE URGENCY OF CULTURAL AWARENESS IN GUIDANCE AND COUNSELING SERVICES] - Maulana, Muhamad Alif; Lessy, Zulkipli (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2023)
Counseling is a process of providing assistance carried out by the counselor as a professional to clients called counselees. In providing counseling assistance there are steps to analyze the problems experienced by the counselee along with their background. The cultural aspect seems to be an important point for consideration in the provision of counseling services. However, in reality, there are still many counselors who ignore the cultural aspects of counselees. This study uses the literature study method by collecting literacy data in accordance with the topic being discussed. Then an analysis was carried out to answer questions about the importance of implementation and cultural awareness in counselors in guidance and counseling services. The results of the study show that the cultural aspect is a very important aspect to consider, in relation to interpreting the counselee's attitude, behavior, and personality and the background of this. Culture is considered an aspect that constructs behavior. Cultural understanding in the counseling process can be used appropriately in rapport and in the assessment process to avoid cultural bias and misinterpretation which will lead to counseling intervention errors.